Pengaruh Inovasi Produk dan Reputasi Perusahaan Dalam Meningkatkan Minat Konsumen Terhadap Jasa Travel Darmawan di Kabupaten Wajo - Agus Purwanto; Suharjum; Asrul Jaya (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2024)
This study aims to determine the effect of product innovation and company reputation on consumer interest in using Darmawan Tour and Umrah and Hajj Travel services in Wajo Regency. This study uses a quantitative approach with a survey method. Data were collected through distributing questionnaires to 76 respondents who had used or were interested in Darmawan Tour services, and analyzed using multiple linear regression with the help of SPSS version 26 software. The results show that both product innovation and company reputation have a positive and significant effect on consumer interest, both partially and simultaneously. The coefficient of determination (R²) value of 53.8% indicates that innovation and reputation together are able to explain the variable of consumer interest by 53.8%, while the remainder is influenced by other variables outside the study. These findings indicate that the combination of innovative services and a good reputation is very important in determining consumer decisions in choosing Umrah and Hajj travel services. This study provides practical implications for Darmawan Tour management to continue to innovate services and maintain and improve the company's reputation in order to maintain and increase consumer loyalty.